Sifat Organoleptik Dan Kadar Air Biskuit Teka Dengan Penambahan Tepung Tempe Kacang Tanah - Yuli Purnamasari; Igde Narda Widiada; Iketut Swirya Jaya; Abdul Salam (Jurnal Gizi Prima (Prime Nutrition Journal), 2017)
Background. NTB province has a prevalence of malnutrition - less ranged from 21,2 percent to 33.1 percent (Agency for Health Research and Development,2013). Feeding ( PMT ) is a form of nutritional interventions to address the problem KEP in infants. One effort that can be given is the addition of tempeh flour biscuits with peanuts. Therefore, it is necessary to study how the organoleptic properties (color,smell,taste,texture) and water content of biscuits with the addition of tempeh peanut flour.Research Methods. Experimental laboratory with experimental design in the form of completely randomized design (CRD) of the factors is the addition of tempeh peanut flour (t) consisting of five cedar treatment repeated 3 times . To test the organoleptic properties of hedonic test method is used while testing the water content gravimetric method.Research Result. The addition of tempeh peanut flour did not Significantly Affect the color, smell, taste (p>0,05) and for the texture Significantly (p<0,05). While the water biscuits levels, the addition of tempeh flour peanut significant effect (p<0,05). The average results of the organoleptic test biscuit color parameters ranged between 3,32 to 3,64 ( approaching the like), odor ranged between 3,36 to 3.68 (approaching the like), taste ranged between 3,28 to 3,76 (approaching the like), texture ranged between 3,16 to 3,64 (approaching the like) and the average test water content ranged between 6,23% - 9,83% not in accordance with SNI.Conclusion. The addition of tempeh peanut flour did not significantly affect the color, smell and taste the biscuits) but real effect on the texture and moisture content of biscuits).